Penerapan E-Learning Berbasis Distance Learning untuk Mengembangkan Life Skill - Eva Luthfi Fakhru Ahsani; Siti Eni Mulyani (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2020)
This study aims to describe online distance learning for students' life skills, especially students in elementary school. The study used a qualitative approach, and the data collection techniques were done through interviews and observations. The sample involved in this study consisted of 14 students from an elementary school. This study indicated that online distance learning through WhatsApp group applications and Education TV programs could develop students' life skills, especially in the covid-19 pandemics time. This online-based distance learning can be done by giving alternative assignments to develop students' life skills while studying at home.